Development of Primary School Curriculum Among Asean Countries (Indonesia, Malaisya, Singapore, Thailand, Cambodia, Brunei Darusalam, and Laos) - Marsella Desriyarini Gui; Fatma Asneni; Rosita Inggile; Reni R. Ahyani; Dina Saripi; Mutiara Pulumuduyo; Ridwan G. Mootalu; Melinda Maula; Sri Meriyanti Daud; Nurhayati Pakaya (International Journal of Advanced Technology and Social Sciences, 2023)
In both developed and developing countries, education is very important. Developed countries see education as a continuous effort to improve the quality of life of their people. Developing countries, on the other hand, need education to catch up with them in the international arena and be on par with developed countries. From this we know that the national curriculum is very important, it is even considered a measure of learning success. This is proven by the fact that the curriculum in Indonesia, Finland, Singapore, Malaysia, Cambodia, Thailand, Brunei Darussalam, the Philippines, Laos, and so on. This research explores various literature related to curriculum from various countries. The national education curriculum was changed several times after independence. This happened in 1947, 1952, 1964, 1968, 1975, 1984, 1994, 2004, 2006, 2013, and 2020, 2022. In curriculum changes, we can find the best curriculum. The Indonesian education curriculum must emphasize the development of Indonesian human character who has faith and devotion to God Almighty. The curriculum is different in Indonesia and several other countries, but these differences are made to improve education in these countries